Genetic resources of vegetable crops: from breeding non-traditional crops to functional food - Yu. V. Fotev; A. M. Artemyeva; O. A. Zvereva (Вавиловский журнал генетики и селекции)
In this review, the authors considered the promising species of vegetable crops for introduction and breeding in the Russian Federation. An attempt was made to assess the possibilities of their breeding improvement from the standpoint of the presence of traits that limit large-scale production. Species that could potentially serve as sources of a high content of functional food ingredients (FFI) have been identified and characterized. For the successful introgression of these species in the Russian Federation, we proposed the methodological approaches including the assessment of the potential cold resistance of thermophilic crops in the mature male gametophyte in vitro (e. g., asparagus bean). The increase in the biodiversity of vegetable plants and improving of their nutritional value should be recognized as one of the main tasks, along with the growth of crop productivity. It is proposed to use the ratio of the total number of the registered cultivars of a particular crop to the number of years since the first cultivar of that crop has been included in the State Register of Breeding Achievements Admitted for Use as a measure of demand. It is advisable to formalize the trait“high content of FFI” in crops, taking as a basis, for example, a 2–4-fold excess of the content of any FFI or their complex in a cultivar over the crop’s standard (reference) value. Such varieties should be included in the State Register of Breeding Achievements Approved for Use as a separate list. The purpose of their separation in the State Register is to ensure the potential interest of investors and business structures in the sale of functional food on the market. The paper discusses in detail the most promising species of introduced vegetable crops from five families (Brassicaceae, Amaranthaceae, Solanaceae, Leguminosae, Cucurbitaceae). The following species are proposed as potential sources of high FPI content: Brassica oleracea ssp. oleracea, B. oleraceae var. alboglabra, B. rapa ssp. chinensis, B. rapa ssp. narinosa, B. rapa ssp. nipposinica, B. rapa ssp. rapa, B. uncea, Cochlearia officinalis, Lepidium sativum, Amaranthus caudatus, A. cruentus, A. hypochondriacus, A. dubius, A. tricolor, lividus, species in the genus Physalis L., Momordica charantia, Benincasa hispida, Cucumis metuliferus, Vigna unguiculata.